2019
DOI: 10.3389/fmicb.2019.02496
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Aspects of an Emerging Poplar Canker Caused by Lonsdalea populi

Abstract: The Gram-negative bacterium Lonsdalea populi causes a lethal disease known as bark canker on Populus × euramericana in China and Europe. Typical symptoms of bark canker include an abundant white-colored fluid, which oozes from the infected tissues. The availability of the genomic sequence of the bacterium provided the necessary resource to launch genome-scale investigations into the mechanisms fundamental to pathogenesis. Functional analyses of a diverse group of genes encoding virulence factors and components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
(40 reference statements)
1
14
0
Order By: Relevance
“…To demonstrate the phylogenetics of L. populi with 12 related bacteria ( Table 3 ), we generated a phylogenetic tree based on single orthologs, which showed that L. populi was closer to Brenneria and Dickeya than to Erwinia ( Figure 4 A). This was consistent with the results of Li and He [ 6 ]. The average nucleotide identity (ANI) values of the 13 genomes were counted using JSpecies software.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…To demonstrate the phylogenetics of L. populi with 12 related bacteria ( Table 3 ), we generated a phylogenetic tree based on single orthologs, which showed that L. populi was closer to Brenneria and Dickeya than to Erwinia ( Figure 4 A). This was consistent with the results of Li and He [ 6 ]. The average nucleotide identity (ANI) values of the 13 genomes were counted using JSpecies software.…”
Section: Resultssupporting
confidence: 94%
“…Infected poplars may die, and entire branches can be broken off by wind [ 5 ]. L. populi has also been reported to naturally infect willow trees ( Salix matsudana ) and causes typical canker symptoms [ 6 ]. Because the bacterium extensively colonizes poplar bark, chemical measures are ineffective for curing and controlling Lonsdalea -infected cankers [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…These diseases, characterized by a canker with white exudates, are confined to the bark of the trunk and branches, primarily in summer [62]. A large percentage of the plantation area of P. × euramericana hybrid poplars in China and Hungary is affected by L. populi, which causes extensive damage to the plantations [63].…”
Section: Phytopathogenic Bacteriamentioning
confidence: 99%
“…populi) Communicated by Erko Stackebrandt. (Toth et al 2013;Li et al 2014;Li and He 2019). Bacteria overwinter on infected plant tissues, in necrosis, gummosis and sap oozing from wounds or healthy looking plant tissues.…”
Section: Introductionmentioning
confidence: 99%